Postharvest quality of eight peach cultivars - Cremasco, João Paulo Gava; Matias, Rosana Gonçalves Pires; Pereira da Silva, Danielle Fabiola; Oliveira, João Alison Alves; Bruckner, Cláudio Horst (Comunicata Scientiae, 2016)
The fruit physical and chemical characteristics can vary during the maturation period and this variation depends, among other factors, on the weather conditions during fruit development. This study aimed to evaluate the changes in physical and chemical characteristics of eight peach cultivars during two seasons. The cultivars Campinas 1, Coral, Maciel, Marli, Premier, Regis, Rei da Conserva and Tropic Beauty were planted on Okinawa rootstock at the experimental orchard of the Federal University of Viçosa (UFV), Viçosa-MG, Brazil, in 2008 and the following characteristics were evaluated: fruit weight, skin color, firmness, soluble solids, titratable acidity, ascorbic acid and total carotenoids. The experiment was conducted during 2011 and 2012 growing seasons in a completely randomized design with eight treatments (cultivars), three repetitions and 10 fruits per plot. There were differences between the variables for the two seasons, with the largest variations observed for firmness, ascorbic acid and total carotenoids. Cultivars Maciel and Marli produced fruit with higher mass, Tropic Beauty with greater firmness and Rei da Conserva, Coral and Marli with higher soluble solids contents. The cultivar Rei da Conserva presented higher values for most of the evaluated variables in both seasons. The yellow color, evaluated by the hue angle, is associated with total carotenoids content in peaches.